Expressive Languages and Narrative (Auto)Biographical Research: Contribuitions to the Teacher Education of Early Childhood Teachers (Olhar de Professor, 2021)
The work brings an account of a doctoral research, in progress since 2017, and discusses the possible dialogues between expressive or poetic languages (art and play) with narrative (auto)biographical research as theoretical and methodological assumptions fundamental to the process training, continuing or in service, of teachers in early childhood education in a municipal education network. In this context, the importance of the aesthetic dimension in the training process is highlighted. As part of the set of methodological procedures carried out, some teaching narratives were reported and the first reflections on the relationship between formation, self-formation, narratives and aesthetic experiences and their repercussions on the pedagogical work developed by teachers and teachers were constructed.
Keywords: Teacher Training. Aesthetic Dimension. Narrative Research.